The Effect of Entrepreneurship Learning and Entrepreneurship Internship on Entrepreneurial Readiness with Motivation as a Mediating Variable among Students of SMKN 2 Batu Malang - Rusno Rusno; Ediyanto Ediyanto; Kristina Sedyastuti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
The purpose of this study is to analyze the effect of entrepreneurship learning and entrepreneurship internship on entrepreneurial readiness, with motivation as a mediating variable among students of SMKN 2 Batu, Malang. This research employs an explanatory design with a quantitative approach. The population consists of 138 students who have participated in entrepreneurship learning and internship programs, with a total of 103 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using WarpPLS version 8.0. The findings reveal that: (1) Entrepreneurship learning has a significant effect on entrepreneurial readiness (P.Value < 0.001, path coefficient = 0.334); (2) Entrepreneurship internship significantly affects entrepreneurial readiness (P.Value < 0.001, path coefficient = 0.292); (3) Motivation has a significant effect on entrepreneurial readiness (P.Value < 0.001, path coefficient = 0.498); (4) Entrepreneurship learning significantly affects entrepreneurial readiness through motivation (P.Value < 0.001, path coefficient = 0.294); and (5) Entrepreneurship internship significantly affects entrepreneurial readiness through motivation (P.Value < 0.001, path coefficient = 0.279). These results indicate that entrepreneurship learning and internships both contribute positively and significantly to students’ entrepreneurial readiness, either directly or indirectly, through enhanced entrepreneurial motivation.